2004
DOI: 10.1002/aic.10275
|View full text |Cite
|
Sign up to set email alerts
|

Resonant geometries for circulation pattern macroinstabilities in a stirred tank

Abstract: Published online in Wiley InterScience (www.interscience.wiley.com). Circulation pattern macroinstabilities and precessing vortices are known to exist in stirred tanks, but until recently they have eluded a full quantitative analysis. In this article, frequency analysis of the axial velocity reveals a resonant frequency and geometry for the 45°pitched-blade turbine (PBT) in a flat-bottom cylindrical tank. Unlike other axial impellers, such as the hydrofoils A310 and HE3, the PBT produces a large-scale circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…at the end of the simulation, the jet returns to be confined within 2L r thus, closing a cycle. This behaviour is consistent with the results of Roussinova et al (2004) who observed a low frequency, high-amplitude variation of the axial velocity in correspondence to both the impeller stream and the wall due to the presence of what they call a "circulation pattern" macro-instability. The radial jet extension is associated with a shift of the core of the two toroidal vortices toward the jet.…”
Section: Resultssupporting
confidence: 91%
“…at the end of the simulation, the jet returns to be confined within 2L r thus, closing a cycle. This behaviour is consistent with the results of Roussinova et al (2004) who observed a low frequency, high-amplitude variation of the axial velocity in correspondence to both the impeller stream and the wall due to the presence of what they call a "circulation pattern" macro-instability. The radial jet extension is associated with a shift of the core of the two toroidal vortices toward the jet.…”
Section: Resultssupporting
confidence: 91%
“…For PBT's, Roussinova et al (2004) reported that circulation pattern instability has one major peak at a frequency f/N =0.186 (N is the impeller rotational speed expressed in revolutions per second). Montes et al (1997) and Hasal et al (2000) obtained f/N= 0.057 for a precessional vortex instability inside a PBT tank at Re= 75,000.…”
Section: Introductionmentioning
confidence: 99%
“…Nikiforaki et al (2003) showed that a long enough sampling time is required to identify clear peaks of MI oscillations from the energy spectrum obtained using an FFT. Roussinova et al (2004) used a wavelet analysis of the time signal to identify the range of frequencies within which MI oscillations occurred. Ducci et al (2008) decomposed MI flow structures for a Rushton impeller STR using POD of the velocity signal to study interaction between MI's of high and low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…We well denote such flow instabilities as jet impingement instabilities (JMIs). In a later investigation Roussinova et al (2004) extended the analysis to different axial impellers. In such work the authors used the LSP method for the spectral analysis.…”
Section: Jet Impingement Macro-instabilities (J-mis)mentioning
confidence: 99%
“…Ducci & Yianneskis, 2007, Roussinova et al, 2004 showed that different kinds of macro-instabilities may be present simultaneously in stirred vessels. For instance Galletti et al (2005b) studied simultaneously with 2-point LDA the combined effect of precessional MIs and flow instabilities stemming from impeller clearance variations (CIs) in different regions of a vessel stirred with a RT.…”
Section: Effect Of Flow Instabilitiesmentioning
confidence: 99%